FRI0552 Patients with Rheumatoid Arthritis Are More Obese than The General Population Already at Disease Onset: A Collaborative Analysis from Three Large German RA Databases. (15th July 2016) - Albrecht, K.; Richter, A.; Callhoff, J.; Huscher, D.; Schett, G.; Zink, A.
Abstract : Background: METARTHROS (Metabolic impact on joint and bone disease) is a nation-wide German network to investigate the interaction between inflammatory and metabolic diseases. Objectives: To compare the distribution of the body mass index (BMI) in early and established rheumatoid arthritis (RA) with representative data from the general population. Methods: The distribution of the BMI was determined with baseline data from the early arthritis cohort CAPEA and the biologics register RABBIT as well as with data of patients enrolled in the National database of the Collaborative Arthritis Centers in 2013. BMI categories of <18.5 kg/m 2 (underweight), 18.5 to <25 kg/m 2 (normal weight), 25 to <30 kg/m 2 (overweight), and ≥30 kg/m 2 (obesity) were used. The results were stratified by age and sex and were compared to the German Ageing Study. The association of the BMI with sociodemographic features and markers of disease activity were analysed with non-parametric tests and linear models. Results: The data of 1, 207 (CAPEA), 12, 230 (RABBIT) and 3, 424 (National database) patients were evaluated. The mean age was 56/56/62 years, the mean disease duration 13 weeks/9.9 years/13.5 years and the mean DAS28 score 5.1/5.2/3.1 units, respectively. In all cohorts, obesity was more frequent (23.8%/23.4%/21.4%) than in the general population (18.2%), remaining in the age groups <70 years, independent of disease duration and more prominent in females (Fig.1 ). Current smoking was inversely associated with BMI. Linear analyses revealed no significant association between BMI and DAS28. Fig.1 Distribution of the BMI in CAPEA, RABBIT and the National database Conclusions: A higher prevalence of obesity, already seen at disease onset, supports a pathogenic role of obesity in the development of RA. This difference is more pronounced in females than in males. Patients in the cohorts with longer disease duration did not show a higher prevalence of obesity than those with recent onset RA, indicating that obesity may rather be a risk factor than a consequence of RA. Acknowledgement: Metarthros is funded by the Federal Ministry of Education and Research (01EC1407D) Disclosure of Interest: None declared